2013
DOI: 10.1017/s0007114513002742
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and lifestyle characteristics associated with normal-weight obesity: the National FINRISK 2007 Study

Abstract: The aim of the present study was to compare the lifestyle (leisure-time physical activity, smoking habits and alcohol consumption) and dietary (energy-yielding nutrients, dietary fibre and foods) factors of Finns with a new syndrome called normal-weight obesity (NWO) with those of lean and overweight Finns. The representative population-based study included 4786 participants (25 -74 years) from the National FINRISK 2007 Study with a health examination and questionnaires. Food intake was assessed using a valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 30 publications
4
41
2
3
Order By: Relevance
“…While NWO studies with actual fitness measures are few, physical inactivity has been suggested to be associated with NWO in former studies [12, 25, 31]. Fewer studies have investigated the associations between dietary intake and NWO and, in agreement with our findings, an association has seldom been found with either amount of energy, the proportion of macronutrients or single nutrients [31, 32].…”
Section: Discussionsupporting
confidence: 84%
“…While NWO studies with actual fitness measures are few, physical inactivity has been suggested to be associated with NWO in former studies [12, 25, 31]. Fewer studies have investigated the associations between dietary intake and NWO and, in agreement with our findings, an association has seldom been found with either amount of energy, the proportion of macronutrients or single nutrients [31, 32].…”
Section: Discussionsupporting
confidence: 84%
“…There seemed to be a declining trend in physical activity as body fat increased, however this did not reach statistical significance. Dietary patterns characterised by low dietary fibre intake, high intake of meat, soft drinks and confectionery have been related to NWO [16]. However, our results showed no significant associations between fruit and vegetable consumption with cardiometabolic outcomes.…”
Section: Discussioncontrasting
confidence: 77%
“…Smoking, physical inactivity and alcohol intake were reported to contribute to cardiometabolic abnormalities [16,27]. Smoking and alcohol were not included in our analyses as less than 0.1% of the respondents reported these behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all cohorts, body weight, height, BMI and waist and hip circumferences were measured as previously described [23,26,27].…”
Section: Other Measurementsmentioning
confidence: 99%